Perdebatan Seputar Isu Jilbab dalam Kitab Tafsir al-Misbah - Azizah Jumriani Narsum; Masyhuri Rifai; Irdawati Saputri; Ni'matuz Zuhra; Nurdin (Gunung Djati Conference Series, 2022)
This study aims to discuss the issue of hijab in the interpretation of al-Misbah. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the thought of Quraish Shihab in the interpretation of al-Misbah, while the material object is the word hijab in the Qur'an. The results and discussion of this study indicate that the hijab issue in the interpretation of al-Misbah includes all types of coverings that can protect women from the views of men who can harass them. This study concludes that the author of the interpretation of al-Misbah seems to interpret the verses of the Qur'an about the hijab according to the context of the homeland with a heterogeneous culture, so that the issue of the hijab is not a matter that must be debated in Indonesia.